Analisis Kelayakan Usaha Pascapanen dan Daya Saing Jahe Simalungun (Jurnal Agribisnis Indonesia, 2023)
Ginger (Zingiber officinale) as a biopharmaceutical plant has been used both as medicine and spice. The export demand for Indonesian ginger can be considered quite high, as just for The Netherlands itself, 40 tons of ginger is needed per month. The study on the analysis of the feasibility and competitiveness of the export ginger post-harvest was carried out as a form of evaluating the competitiveness and feasibility of the post-harvest that had been carried out. The purpose of this study is analyzing production costs in rupiah and USD, income earned in rupiah and USD, local resource costs in rupiah and USD, import resource costs in rupiah and USD, the competitiveness of ginger in the international market and also the postharvest business feasibility of exported ginger in the research area. The cost analysis method is the method used to calculate production costs, income, domestic resource costs, and imported resource costs in this study. Business feasibility analyzed with Break Even Point (BEP) and the competitiveness of exported ginger in the international market analyzed with the domestic resource cost method. The conclusion of the study showed that Simalungun ginger has an ability to be competitive and compete in the international market and provide benefits and feasible to continue.